IDENTIFIKASI KEARIFAN LOKAL TENTANG TEKNIK PENANGKAPAN BURUNG DI DESA RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR - Affhart Chata; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the local wisdom of bird catching techniques in the village rumbio. This research conducted at the Forest in village Rumbio, subdistrict kampar, district kampar. The research was conducted in December 2014 with a qualitative descriptive method. Data collected by interviews or debriefing with the respondent. The sampling technique used in this research is the Snowball Sampling. The question posed is open for the purpose of providing an opportunity for respondents to express their opinions. the interview process will be documented in the form of written notes, photographs and recording devices. Based on the results of the research showed that the kuaran bird catching technique in the Village Rumbio with traps or summon a bird and then the birds kuaran invited to play. Habits of the people in the village Rumbio in catching birds kuaran the hereditary creates a form of the local wisdom, namely: the span of the arrest, a tool used traditionally, one bird species arrested, the number of birds who was arrested small ± 10, do not damage the ecosystem and arrests still to preserve bird habitats.   Keywords: the local wisdom, bird catching technique, district Kampar